Multi-objective optimization of SOI-based Mach-Zehnder modulators employing deep neural networks and a non-dominant genetic algorithm - De Paula, Romulo; Sutili, Tiago; Figueiredo, Rafael C.; Bustamante, Yesica R. R.; Hernandez-Figueroa, Hugo Enrique; Abreu, Leandra [UNESP]; Aldaya, Ivan [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
We combine an artificial neural network model of an integrated Mach-Zehnder modulator with a multi-objective optimization algorithm to optimize the modulator's parameters. The use of a multi-objective algorithm leads to a set of non-dominant optimized configurations with different values of figures of merit.
Keywords: Mach-Zehnder modulator; Optimization; SOI